Lithium-rich manganese-based positive electrode material and preparation method thereof, positive electrode and battery

By forming a cladding layer of lithium salt compounds and interface protective layer substances on the lithium-rich manganese-based positive electrode material, the problem of cell inflation and voltage attenuation of the material is solved, high specific capacity and cyclic stability are achieved, and the next generation of lithium is met Market demand for ion batteries.

CN119170776APending Publication Date: 2024-12-20SUZHOU AMIT MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411394325.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based cathode materials have problems such as low first effect, serious battery cell gas production and voltage attenuation in commercial applications, which is difficult to meet the market demand of next-generation lithium-ion batteries.

Method used

Using a heterostructure composed of lithium salt compounds, interface protective layer substances and lithosaline-rich lithium-manganese-based substances, the interface protective layer and surface treatment initiating substances to form a stable structure, reducing the contact between the electrode material and the electrolyte, and inhibiting the Interface side reactions and improve the circulation stability of the material through the sintering process.

Benefits of technology

It achieves high charge and discharge specific capacity and cycle stability, effectively solves the problems of cell inflation and voltage attenuation, and improves the circulation performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, in particular to a lithium-rich manganese-based positive electrode material, a preparation method thereof, a positive electrode and a battery. The active material in the positive electrode material is coated by the coating layer, and the coating layer is formed by the interface protection layer substance, the surface treatment initiator substance and the active material, so that on one hand, the interface protection layer formed by the interface protection layer substance can effectively reduce the dissolution of transition metal ions; the direct contact between the electrode material and the electrolyte can be prevented, and the generation of interface side reaction is effectively inhibited; on the other hand, the interface protection layer substance and the surface treatment initiation substance can react with residual lithium on the surface layer of the active material to form a stable structure or cause benign transformation of the material surface structure. Tests show that the 0.1 C charging specific capacity of the lithium-rich manganese-based positive electrode material provided by the invention reaches 320 mAh / g or above, the 0.1 C discharging specific capacity reaches 249 mAh / g or above, and the 100-week cycle retention rate is maintained to be 100% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode and a battery. Background Art

[0002] The current commercial cathode material, LiCoO 2 As the first cathode material for commercial LIBs, it has a high operating voltage and is easy to prepare, but its high cost and toxicity limit its large-scale application; alternative LiMn 2 O 4 , LiFePO 4 ,LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 and LiNi 0.8 Co 0.15 Mn 0.05 O 2 Although some breakthroughs have been made in the research of positive electrode materials, all of which have a capacity of 120~210 mAh / g, the energy density of the above materials is usually less than 300 Wh / kg, which is difficult to meet the market demand for the next generation of LIBs.

[0003] From the current technology, the energy density of batteries can be increased by reducing the mass ratio of inactive substances in the battery cells, which has almost reached the limit of technology. The use of positive and negative electrode materials with higher energy density is the most direct technical approach to increase the energy density of batteries. It is estimated that by 2025, the specific capacity of positive electrode materials will need to be increased to more than 250 mAh / g. In order to meet national requirements, the specific capacity of positive electrode materials may even need to reach more than 300 mAh / g. The theoretical material energy density of lithium-rich manganese-based materials is also the highest based on existing positive electrode materials. Lithium-rich manganese-based positive electrodes are one of the material systems that meet the high specific energy requirements. However, lithium-rich manganese-based positive electrode materials also have low initial efficiency, severe gas production in the battery cells, and severe voltage decay, which restricts their commercialization process.

[0004] Through strategies such as doping, coating, and surface treatment, the structure and surface stability of lithium-rich materials can be effectively stabilized, thereby improving cycle performance, inhibiting high-temperature gas production, and inhibiting voltage decay. For example, Chinese patent CN114744182A discloses a modified cobalt-free lithium-rich manganese-based positive electrode material co-doped with molybdenum and sulfur and a preparation method thereof. Through the sol-gel method, molybdenum and sulfur elements replace the transition metal elements and oxygen elements in the material to increase Li + Diffused interlayer spacing and improved Li + The structural changes during the deintercalation process improve the initial coulombic efficiency and cycle stability of the material. However, the overall preparation process is complicated, which is not conducive to engineering scale-up, and cannot solve problems such as voltage attenuation and battery cell bloating.

[0005] For example, Chinese patent CN114566636B discloses a lithium-rich manganese-based positive electrode material, a preparation method and use thereof. The method adopts double-layer coating and other methods to improve the lithium-rich manganese-based material, including a first coating and a second coating. The first coating includes a composite oxide of Al, Zr, Ce and La and an n-type thermoelectric material, and the second coating includes a composite carbon material, a hydrogen-containing lithium titanium oxide compound and molybdenum disulfide, etc., which improves the discharge specific capacity, rate efficiency and cycle stability of the material. However, the prepared coating layer is too complicated and difficult to achieve industrialization. It solves some problems of the lithium-rich manganese-based material, but the core problem of battery cell bloating and voltage attenuation has not been solved. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode and a battery. The lithium-rich manganese-based positive electrode material provided by the present invention has a high charge and discharge specific capacity and high cycle stability.

[0007] The present invention provides a lithium-rich manganese-based positive electrode material, comprising an active material and a coating layer coated on the surface of the active material;

[0008] The coating layer comprises a lithium salt compound, an interface protective layer material and a rock salt phase lithium-rich manganese-based material, wherein the lithium salt compound and the rock salt phase lithium-rich manganese-based material form a heterogeneous structure;

[0009] The rock salt phase lithium-rich manganese-based material includes one or more of a disordered rock salt structure or a rock salt structure;

[0010] The lithium salt compounds include lithium molybdate, lithium niobate, lithium phosphate, lithium aluminate, lithium dihydrogen phosphate, lithium borate, LATP, LLZO, LLTO, LLZTO, Li 2 ZrO 3 , Li 4 Ti 5 O 12 、LiCoPO 4 One or more of;

[0011] The interface protection layer material includes Al 2 O 3 、MgO、SnO 2 、CeO 2 , AlF 3 , CoF 2 MgF 2 、CePO 4 , polyethylenedioxythiophene, Li 2 ZrO 3 , Li 4 Ti 5 O12 、LiCoPO 4 、MnO 2 , Nb 2 O 5 、Co 3 O 4 , LATP, LLZO, LLTO and LLZTO;

[0012] The surface treatment initiating substance includes MoS 2 、SiO 2 , phosphate, oxalic acid, phosphoric acid, boric acid, ammonium bicarbonate, ammonium sulfate and carbon dioxide.

[0013] The lithium-rich manganese-based positive electrode material provided by the present invention includes an active material, wherein the active material includes a polycrystalline aggregate lithium-rich manganese-based material and a quasi-single-crystal lithium-rich manganese-based material. More specifically, the active material is a compound having a structure shown in Formula I;

[0014] Li 1+x Ni y Co z Mn a M b O 2 Formula I;

[0015] Wherein, the M is selected from Mg, Al, Ta, Ca, Ti, Zr, B, Nb, W, M O , Fe, Cr, Zn, Na or Cu;

[0016] 0.08≤x≤0.26, 0.10≤y≤0.32, 0≤z≤0.15, 0.45≤a≤0.66, 0≤b≤0.05.

[0017] The lithium-rich manganese-based positive electrode material provided by the present invention also includes a coating layer coated on the surface of the active material, and the coating layer is formed by the reaction of an interface protection layer material, a surface treatment initiating material and the active material. The mass ratio of the interface protection layer material and the surface treatment initiating material of the present invention is (0.0001~5):(0.0001~5), preferably (0.01~2):(0.01~2). The mass content of the coating layer of the present invention in the lithium-rich manganese-based positive electrode material is 0.0002 wt%~10 wt%.

[0018] The interface protection layer material of the present invention includes Al 2 O 3 、MgO、SnO 2 、CeO 2 , AlF 3 , CoF 2 MgF2 、CePO 4 , polyethylenedioxythiophene, Li 2 ZrO 3 , Li 4 Ti 5 O 12 、LiCoPO 4 、MnO 2 , Nb 2 O 5 、Co 3 O 4 , Li 1.3 AI 0.3 Ti 1.7 (PO 4 ) 3 (referred to as LATP), Li 7 La 3 Zr 2 O 12 (LLZO for short), Li 0.33 La 0.56 TiO 3 (LLTO) and Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (abbreviated as LLZTO) in one or more, wherein according to the mechanism of action, the Al 2 O 3 、MgO、SnO 2 、CeO 2 , AlF 3 , CoF 2 MgF 2 and CePO 4 can be divided into inert coating materials, the polyethylene dioxythiophene can be divided into electronic conductive coating materials, the Li 2 ZrO 3 , Li 4 Ti 5 O 12 and LiCoPO 4 It can be divided into ion conductive coating materials, the MnO 2 , Nb 2 O 5 and Co 3 O 4 The surface treatment initiating material of the present invention includes MoS 2 、SiO 2, phosphate, oxalic acid, phosphoric acid, boric acid, ammonium bicarbonate, ammonium sulfate and carbon dioxide. The active material of the present invention is the same as the above, and will not be described in detail.

[0019] On the one hand, the present invention forms an interface protection layer by the interface protection layer material to prevent direct contact between the electrode material and the electrolyte, and effectively inhibit the occurrence of interface side reactions; on the other hand, the surface treatment initiating substance and the interface protection layer substance react with the residual lithium on the surface of the active material to form a substance with a stable structure or a substance that can cause a benign transformation of the surface structure of the material, specifically, a lithium salt compound and a rock salt phase lithium-rich manganese-based substance are formed by the reaction, and the lithium salt compound and the rock salt phase lithium-rich manganese-based substance positive electrode material form a heterogeneous structure, and the lithium salt compound and the rock salt phase lithium-rich manganese-based substance are the same as above, and no further description is given; in addition, it is specifically stated that the lithium salt compound may include LATP, LLZO, LLTO, LLZTO, Li 2 ZrO 3 , Li 4 Ti 5 O 12 、LiCoPO 4 It is additionally formed by the reaction of the interface protection layer substance, the surface treatment initiating substance and the active material, and is not the raw material of the interface protection layer substance itself.

[0020] The present invention also provides a method for preparing the lithium-rich manganese-based positive electrode material described in any of the above technical solutions, comprising the following steps: sintering the active material, the interface protection layer material and the surface treatment initiating material under a special gas atmosphere to obtain the lithium-rich manganese-based positive electrode material. The special gas described in the present invention is selected from one or more of ammonia, carbon dioxide, argon and nitrogen.

[0021] Specifically, the present invention mixes the active material, the interface protection layer material and the surface treatment initiating material to obtain a mixed powder; then the mixed powder is sintered under a special gas atmosphere to obtain the lithium-rich manganese-based positive electrode material. The mixing method described in the present invention is dry mixing. The active material, the interface protection layer material and the surface treatment initiating material described in the present invention are the same as those described above and will not be repeated. In some embodiments of the present invention, the amount of the interface protection layer material added is 0.0001 wt%~5 wt% of the mixed powder, and further 0.01 wt%~2 wt%; the amount of the surface treatment initiating material added is 0.0001 wt%~5 wt% of the mixed powder, and further 0.01 wt%~2 wt%.

[0022] In the present invention, the mixed powder is sintered and then naturally cooled to room temperature to obtain the lithium-rich manganese-based positive electrode material. The sintering temperature of the present invention is 300°C to 700°C, further 350°C to 600°C, and the sintering time is 1 h to 10 h, further 3 h to 7 h.

[0023] The active material of the present invention is prepared by the following steps:

[0024] S1) reacting a Ni source, a Co source, a Mn source, an M source and a precipitant in the presence of a complexing agent to obtain a lithium-rich manganese-based positive electrode material precursor;

[0025] S2) calcining the lithium-rich manganese-based positive electrode material precursor obtained in step S1) and a Li source to obtain the active material.

[0026] The present invention firstly uses a coprecipitation reaction to obtain a lithium-rich manganese-based positive electrode material precursor, that is, in the presence of a complexing agent, a Ni source, a Co source, a Mn source, an M source and a precipitant are reacted to obtain a lithium-rich manganese-based positive electrode material precursor; specifically, a sulfate solution of a Ni source, a sulfate solution of a Co source, a sulfate solution of a Mn source, a soluble salt solution of an M source, a precipitant and a complexing agent are mixed for a coprecipitation reaction to obtain a lithium-rich manganese-based positive electrode material precursor. The precipitant of the present invention is selected from one or more of sodium carbonate, sodium bicarbonate, ammonium bicarbonate and sodium hydroxide; the complexing agent is selected from one or more of ammonia water or oxalic acid.

[0027] After obtaining the lithium-rich manganese-based cathode material precursor, the present invention calcines the obtained lithium-rich manganese-based cathode material precursor and a Li source to obtain an active material. Specifically, the present invention mixes the obtained lithium-rich manganese-based cathode material precursor and a Li source according to a molar ratio of Li / Me of 1 to 1.8 of the final active material, and calcines to obtain an active material; preferably, the mixture is mixed according to a molar ratio of Li / Me of 1.28 to 1.55, wherein Me refers to Ni, Co, Mn and M atoms. The Li source of the present invention is selected from one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium oxalate and lithium acetate.

[0028] The calcination of the present invention is carried out in an oxygen-containing gas atmosphere, specifically in an oxygen or air atmosphere. The calcination of the present invention is specifically: the mixture obtained by pre-calcining at 300°C to 700°C for 1 h to 10 h, heating to 600°C to 1000°C and keeping warm for 6 h to 24 h. In certain embodiments of the present invention, the calcination is specifically: pre-calcining at 350°C to 600°C for 2 h to 5 h, heating to 800°C to 980°C and keeping warm for 10 h to 20 h. The present invention performs calcination and naturally cools to room temperature to obtain the active material.

[0029] The present invention also provides a positive electrode, comprising a current collector and a lithium-rich manganese-based positive electrode material according to any of the above technical solutions disposed on the current collector. In certain embodiments of the present invention, the present invention coats the lithium-rich manganese-based positive electrode material according to any of the above technical solutions on the current collector to obtain a positive electrode sheet. The present invention has no special limitation on the current collector.

[0030] The present invention also provides a battery, comprising a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode; the positive electrode comprises a current collector and the lithium-rich manganese-based positive electrode material described in any of the above technical solutions disposed on the current collector. The present invention has no special limitation on the negative electrode and the separator.

[0031] The present invention provides a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode and a battery. The active material in the lithium-rich manganese-based positive electrode material provided by the present invention is coated by a coating layer, and the coating layer is formed by an interface protection layer material and a surface treatment initiator material, wherein the interface protection layer formed by the interface protection layer material can effectively reduce the dissolution of transition metal ions, and can also prevent the electrode material from directly contacting the electrolyte, effectively inhibiting the occurrence of interface side reactions. The surface treatment initiator can react with the residual lithium on the surface of the active material to form a stable structure or can cause a benign transformation of the surface structure of the material, such as MoS 2 At high temperature, it can slowly oxidize with oxygen to generate molybdenum oxide and sulfur dioxide. The sulfur element replaces part of the oxygen on the surface, strengthens the binding force of oxygen, reduces the release of oxygen, and further alleviates flatulence and voltage decay. In addition, molybdenum oxide can react with alkali to further generate ammonium molybdate and other substances. The high-priced Mo 6+ It not only forms a fast ion conductive layer of lithium molybdate with the residual lithium on the surface, but can also epitaxially grow an interface layer similar to the rock salt structure. The material particles form a composite structure from the outside to the inside that includes an interface protective layer of aluminum oxide, lithium molybdate, a rock salt-like structure and a layered structure, which can significantly improve the material's voltage attenuation, battery cell bloating, initial efficiency and cycle stability.

[0032] Experiments show that the 0.1C charging specific capacity of the lithium-rich manganese-based positive electrode material provided by the present invention reaches more than 320 mAh / g, the 0.1C discharge specific capacity reaches more than 249 mAh / g, and the 100-cycle cycle retention rate is maintained at more than 100%. It can effectively take into account the stability of the structure and the surface to solve the problems of cycle stability, battery cell flatulence, voltage decay and the like of the lithium-rich manganese-based material in practical applications, thereby having high charge and discharge specific capacity and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the positive electrode material obtained in Example 1 of the present invention;

[0034] Figure 2This is a SEM image of the positive electrode material obtained in Comparative Example 1 of the present invention;

[0035] Figure 3 It is a comparison diagram of the charge and discharge curves of Example 1 of the present invention and Comparative Example 1;

[0036] Figure 4 It is a cycle comparison diagram of Example 1 of the present invention and Comparative Example 1;

[0037] Figure 5 It is a comparison chart of gas production of the full battery soft pack of Example 1 of the present invention and Comparative Example 1 after 200 cycles. DETAILED DESCRIPTION

[0038] The present invention discloses a lithium-rich manganese-based positive electrode material and a preparation method thereof, a positive electrode and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0039] The present invention will be further described below in conjunction with embodiments:

[0040] Example 1

[0041] The positive electrode material prepared in this embodiment is Li 1.2 Ni 0.28 Mn 0.52 O 2 , and its preparation method comprises the following steps:

[0042] (1) Preparation of lithium-rich manganese-based cathode material precursor Ni by co-precipitation method 0.35 Mn 0.65 (OH) 2 ;

[0043] (2) The obtained precursor is mixed with lithium salt in a molar ratio of Li / Me=1.5, pre-calcined at 500°C for 3 h in an air atmosphere, heated to 900°C and kept at that temperature for 12 h, and naturally cooled to room temperature to obtain a primary product of lithium-rich manganese-based positive electrode material;

[0044] (3) 1500 ppm AlF 3 and 3000 ppm of LATP and 1500 ppm of MoS as surface treatment initiator 2 Mixing with a primary product of a lithium-rich manganese-based positive electrode material by a dry method to obtain a composite coated lithium-rich manganese-based positive electrode material mixed powder;

[0045] (4) The obtained composite coated lithium-rich manganese-based positive electrode material mixed powder was sintered at 650°C for 6 h in an ammonia atmosphere and naturally cooled to room temperature to obtain a composite coated lithium-rich manganese-based positive electrode material. The positive electrode material was microscopically characterized. The results are as follows: Figure 1 As shown, Figure 1 This is a SEM image of the positive electrode material obtained in Example 1 of the present invention.

[0046] Example 2

[0047] The positive electrode material prepared in this embodiment is Li 1.2 Ni 0.28 Mn 0.52 O 2 , and its preparation method comprises the following steps:

[0048] (1) Preparation of lithium-rich manganese-based cathode material precursor Ni by co-precipitation method 0.35 Mn 0.65 (OH) 2 ;

[0049] (2) The obtained precursor is mixed with lithium salt in a molar ratio of Li / Me=1.5, pre-calcined at 500°C for 3 h in an air atmosphere, heated to 900°C and kept at that temperature for 12 h, and naturally cooled to room temperature to obtain a primary product of lithium-rich manganese-based positive electrode material;

[0050] (3) 1500 ppm Al 2 O 3 and 3000 ppm of LATP and 1500 ppm of MoS as surface treatment initiator 2 Mixing with a primary product of a lithium-rich manganese-based positive electrode material by a dry method to obtain a composite coated lithium-rich manganese-based positive electrode material mixed powder;

[0051] (4) The obtained composite coated lithium-rich manganese-based positive electrode material mixed powder was sintered at 650°C for 6 h in an ammonia atmosphere and naturally cooled to room temperature to obtain a composite coated lithium-rich manganese-based positive electrode material.

[0052] Example 3

[0053] The positive electrode material prepared in this embodiment is Li 1.2 Ni 0.28 Mn 0.52 O 2 , and its preparation method comprises the following steps:

[0054] (1) Preparation of lithium-rich manganese-based cathode material precursor Ni by co-precipitation method 0.35 Mn 0.65 (OH) 2 ;

[0055] (2) The obtained precursor is mixed with lithium salt in a molar ratio of Li / Me=1.5, pre-calcined at 500°C for 3 h in an air atmosphere, heated to 900°C and kept at that temperature for 12 h, and naturally cooled to room temperature to obtain a primary product of lithium-rich manganese-based positive electrode material;

[0056] (3) 1500 ppm Al 2 O 3 and 3000 ppm Nb 2 O 5 and surface treatment initiating substances 1500 ppm MoS 2 Mixing with a primary product of a lithium-rich manganese-based positive electrode material by a dry method to obtain a composite coated lithium-rich manganese-based positive electrode material mixed powder;

[0057] (4) The obtained composite coated lithium-rich manganese-based positive electrode material mixed powder was sintered at 650°C for 6 h in an ammonia atmosphere and naturally cooled to room temperature to obtain a composite coated lithium-rich manganese-based positive electrode material.

[0058] Example 4

[0059] The positive electrode material prepared in this embodiment is Li 1.2 Ni 0.28 Mn 0.52 O 2 , and its preparation method comprises the following steps:

[0060] (1) Preparation of lithium-rich manganese-based cathode material precursor Ni by co-precipitation method 0.35 Mn 0.65 (OH) 2 ;

[0061] (2) The obtained precursor is mixed with lithium salt in a molar ratio of Li / Me=1.5, pre-calcined at 500°C for 3 h in an air atmosphere, heated to 900°C and kept at that temperature for 12 h, and naturally cooled to room temperature to obtain a primary product of lithium-rich manganese-based positive electrode material;

[0062] (3) 1500 ppm AlF 3 and 3000 ppm of LATP and 1000 ppm of MoS as surface treatment initiator 2 and 1000 ppm of ammonium bicarbonate are mixed with the primary product of the lithium-rich manganese-based positive electrode material by a dry method to obtain a composite coated lithium-rich manganese-based positive electrode material mixed powder;

[0063] (4) The obtained composite coated lithium-rich manganese-based positive electrode material mixed powder was sintered at 650°C for 6 h in an ammonia atmosphere and naturally cooled to room temperature to obtain a composite coated lithium-rich manganese-based positive electrode material.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that 1500 ppm of AlF 3 and 3000 ppm of LATP, without adding surface treatment initiating substances 1500 ppm of MoS 2 , other conditions and parameters are exactly the same as those in Example 1.

[0066] The obtained cathode material was characterized microscopically. Figure 2 As shown, Figure 2 This is a SEM image of the positive electrode material obtained in Comparative Example 1 of the present invention.

[0067] Comparative Example 2

[0068] The only difference between this comparative example and Example 1 is that 1500 ppm of MoS 2 , other conditions and parameters are exactly the same as those in Example 1.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 1 is that 1500 ppm of AlF 3 and 3000 ppm of LATP, and other conditions and parameters were exactly the same as in Example 1.

[0071] The positive electrode materials of the above Examples 1-4 and Comparative Examples 1-3 were respectively made into pole pieces to be assembled into liquid lithium-ion batteries as working electrodes for charge and discharge tests. The first discharge specific capacity and first coulomb efficiency were tested at a voltage range of 2.0-4.8V, 0.1C / 0.1C, and the 100-cycle capacity retention rate was tested at 2.0-4.6V, 1C / 1C. The results are shown in Table 1. Figures 3-5 As shown, Figure 3 It is a comparison diagram of the charge and discharge curves of Example 1 of the present invention and Comparative Example 1, Figure 4 It is a cycle comparison diagram of Example 1 of the present invention and Comparative Example 1, Figure 5 It is a comparison chart of gas production of the full battery soft pack of Example 1 of the present invention and Comparative Example 1 after 200 cycles.

[0072] Table 1

[0073]

[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A lithium-rich manganese-based positive electrode material, characterized in that: It includes an active material and a coating layer coated on the surface of the active material; The coating layer comprises a lithium salt compound, an interface protective layer material and a rock salt phase lithium-rich manganese-based material, wherein the lithium salt compound and the rock salt phase lithium-rich manganese-based material form a heterogeneous structure; The rock salt phase lithium-rich manganese-based material includes one or more of a disordered rock salt structure or a rock salt structure; The lithium salt compounds include lithium molybdate, lithium niobate, lithium phosphate, lithium aluminate, lithium dihydrogen phosphate, lithium borate, LATP, LLZO, LLTO, LLZTO, Li2ZrO3, Li4Ti5O 12 , one or more of LiCoPO4; The interface protection layer material includes LATP, LLZO, LLTO, LLZTO, Li2ZrO3, Li4Ti5O 12 , LiCoPO4, Al2O3, MgO, SnO2, CeO2, AlF3, CoF2, MgF2, CePO4, polyethylenedioxythiophene, MnO2, Nb2O5 and Co3O4.

2. A lithium-rich manganese-based positive electrode material, characterized in that: It includes an active material and a coating layer coated on the surface of the active material; The coating layer is formed by the reaction of the interface protection layer material, the surface treatment initiating material and the active material; The interface protection layer material includes Al2O3, MgO, SnO2, CeO2, AlF3, CoF2, MgF2, CePO4, polyethylene dioxythiophene, Li2ZrO3, Li4Ti5O 12 , LiCoPO4, MnO2, Nb2O5, Co3O4, LATP, LLTO, LLZO and LLZTO; The surface treatment initiating substance includes one or more of MoS2, SiO2, phosphate, oxalic acid, phosphoric acid, boric acid, ammonium bicarbonate, ammonium sulfate and carbon dioxide.

3. The lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The mass ratio of the interface protection layer material to the surface treatment initiating material is (0.0001-5): (0.0001-5).

4. The lithium-rich manganese-based positive electrode material according to claim 1, 2 or 3, characterized in that: The mass content of the coating layer in the lithium-rich manganese-based positive electrode material is 0.0002 wt%~10 wt%.

5. The lithium-rich manganese-based positive electrode material according to claim 1, 2 or 3, characterized in that: The active material is a compound with a structure shown in Formula I; Li 1+x Ni y Co z Mn a M b O2 of formula I; Wherein, M is selected from one or more of Mg, Al, Ta, Ca, Ti, Zr, B, Nb, W, Mo, Fe, Cr, Zn, Na or Cu; 0.08≤x≤0.26, 0.10≤y≤0.32, 0≤z≤0.15, 0.45≤a≤0.66, 0≤b≤0.

05.

6. A method for preparing the lithium-rich manganese-based positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: In a special gas atmosphere, sintering the active material, the interface protection layer material and the surface treatment initiating material to obtain the lithium-rich manganese-based positive electrode material; The special gas is selected from one or more of ammonia, carbon dioxide, argon and nitrogen.

7. The preparation method according to claim 6, characterized in that: The sintering temperature is 300° C. to 700° C., and the sintering time is 1 h to 10 h.

8. The preparation method according to claim 6, characterized in that: The active material is prepared by the following steps: S1) reacting a sulfate solution of a Ni source, a Co source, a Mn source and a M source with a precipitant in the presence of a complexing agent to obtain a lithium-rich manganese-based positive electrode material precursor; S2) calcining the lithium-rich manganese-based positive electrode material precursor obtained in step S1) and a Li source to obtain the active material.

9. A positive electrode, characterized in that: The invention comprises a current collector and a lithium-rich manganese-based positive electrode material as claimed in any one of claims 1 to 5 arranged on the current collector.

10. A battery, characterized in that: It includes a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode; The positive electrode comprises a current collector and a lithium-rich manganese-based positive electrode material according to any one of claims 1 to 5 arranged on the current collector.

Citation Information

Patent Citations

  • A lithium-rich manganese-based cathode material, its preparation method and applications

    CN114566636B

  • Molybdenum and sulfur co-doped modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN114744182A

Cited By

  • Modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN121964604A

  • A lithium-rich manganese-based positive electrode material with a functional coating layer and a preparation method thereof

    CN122843342A